1989
DOI: 10.1002/bscb.19890980803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Imines From N‐(1‐Halogenoalkyl)Heteroarylium Salts

Abstract: SYNTHESIS OF IMINES FROM N-(1-HALOGEN0ALKYL)HETEROARYLlUM SALTSABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Aldehydes are known to react with N,N'-dimethyl-and N,N'-diphenyl-1,2-ethanediamines to yield imidazolidines. ', In our hands N-(1-chloroalky1)pyridinium chlorides la-h behave similarly and imidazolidines [4][5][6][7][8][9][10][11][12] (Table) were isolated in good yields. Optimalization of the experimental conditions was achieved on the basis of the nmr data.…”
Section: Resultsmentioning
confidence: 62%
“…Aldehydes are known to react with N,N'-dimethyl-and N,N'-diphenyl-1,2-ethanediamines to yield imidazolidines. ', In our hands N-(1-chloroalky1)pyridinium chlorides la-h behave similarly and imidazolidines [4][5][6][7][8][9][10][11][12] (Table) were isolated in good yields. Optimalization of the experimental conditions was achieved on the basis of the nmr data.…”
Section: Resultsmentioning
confidence: 62%
“…HSQC confirms that the singlet in the 1 H NMR spectrum assigned to CClH (δ 6.58 ppm) is coupled to a strongly deshielded sp 3 carbon at δ 91 ppm, which diverges substantially from both 3 a and from previously reported azaallenium complexes, instead aligning more closely with previously reported N-chloroalkylpyridinium salts. [44] Density functional theory (DFT) modeling of the azaallenium energies at the B3LYP-D3/6-311 + g(d,p)-(C,H,N,Cl)/SDD(Os)-PCM(MeCN)//B3LYP-D3/6-31g(d)-(C,H,N,Cl)/SDD(Os)-PCM(MeCN) level of theory show a stark decrease in stability of the azaallenium isomer relative to the aza-allyl chloride upon introduction of the methyl groups, presumably due to steric clashes between the methyl groups and the equatorial ligands (see Supporting Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed preparation of 13-imidazopyridines, which are known to be potent cardiotonic agents,'& often requires drastic conditions like prolonged heating in polyphosphoric acid. ", *'Thus, we found that treatment of 4-methylbenzaldehyde with a mixture of thionyl chloride and pyridine in dichloromethane, followed by reaction with 2,3-pyridinediamine (three equivalents) produced 3-[(4-methylphenyl)-methylene1amin0-2-pyridineamine(5). We reasonedthat experimental conditions were too mild to effect the conversion of the imine into the imidazopyridine system.…”
mentioning
confidence: 99%